Erosion of rocky shore platforms by block detachment from layered stratigraphy. Issue 4 (18th January 2020) - Buchanan, Danielle H.; Naylor, Larissa A.; Hurst, Martin D.; Stephenson, Wayne J.
Abstract: The majority of shore platforms form in rocks that are characterised by layered stratigraphy and pervasive jointing. Plucking of weathered, joint and bed bounded blocks is an important erosion process that existing models of platform development do not represent. Globally, measuring platform erosion rates have focused on microscale (< 1 mm) surface lowering rather than mesoscale (0.1‐1 m) block detachment, yet the latter appears to dominate the morphological development of discontinuity rich platforms. Given the sporadic nature of block detachment on platforms, observations of erosion from storm event to multi‐decadal timescales (and beyond) are required to quantify shore platform erosion rates. To this end, we collected aerial photography using an unmanned aerial vehicle to produce structure‐from‐motion‐derived digital elevation models and orthophotos. These were combined with historical aerial photographs to characterise and quantify the erosion of two actively eroding stratigraphic layers on a shore platform in Glamorgan, south Wales, UK, over 78‐years. We find that volumetric erosion rates vary over two orders of magnitude (0.1‐10 m 3  yr ‐1 ) and do not scale with the length of the record. Average rates over the full 78‐year record are 2‐5 m 3  yr ‐1 . These rates are equivalent to 1.2‐5.3 mm yr ‐1 surface lowering rates, an order of magnitude faster than previously published, both at our site and around the world in similar rock types. We show that meso‐scale platform erosion via block detachment processes is a dominant erosion process on shore platforms across seasonal to multi‐decadal timescales that have been hitherto under‐investigated. © 2019 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Platform erosion via block detachment is a dominant process on discontinuity‐rich shore platforms across seasonal to multi‐decadal scales. We find that average erosion rates over a 78‐year period are 2‐5 m 3  yr ‐1 ; which are an order of magnitude greater than previous measurements quantifying mm‐scale vertical surface lowering, both at our site and around the world in similar rock types.